Effect of primary astigmatism on the tight focusing of ellipse field singularities - Pal S.K.; Singh R.K.; Senthilkumaran P. (My University, 2025)
The tight focusing of ellipse field singularities, namely bright and dark C-points, is studied using the Debye–Wolf diffraction integral in the presence of primary astigmatism. The effect of polarization distribution, the sign of polarization singularity index, amplitude, and handedness of the ellipse field singularities are investigated in the intensity distribution of the focal plane of a high numerical aperture lens system in the presence of primary astigmatism. Ellipse field singularities that are tightly focused can create an additional longitudinal component at the focal plane. At the focal plane, both the longitudinal and transverse components of the ellipse fields are found to be hosted with phase vortices of charge ±1. In the presence of primary astigmatism, the helicity inversion of input C-point does not rotate the focal plane intensity distributions by 180°. © 2023 Elsevier Ltd